Breastfeeding Practices: A Cross-Believed Perspective - Fathullah Harun, Hanifah Musa; Md. Rejab, Siti Noorbiah; Samori, Zakiah (Advances in Social Sciences Research Journal, 2017)
Breastfeeding practices have been so common among Muslim mothers in the community that children are breastfed even after their baby phase. Breastfeeding can contribute to mental and physical growth of children. The significance and benefits of breast milk have not only been recognized in Islam, but also by medical science and nutrition research. This article aims to discuss the infant feeding practices based on religious and scientific foundation in the Muslim community, with a primary focus on the advantages of breastfeeding as well as syariah-related issues on breastfeeding. The research methodology used in this paper is the analysis of books and papers related to breastfeeding. The results of this discussion have confirmed the benefits of breastfeeding from the Islamic and scientific perspectives.